Alora Graf: capstone - Graf, Alora, artist (Colorado State University. Libraries, 2025)
The artist's statement: My approach to graphic design bridges typographic systems with the human aspect of creating a brand or design project. I have attained a degree in drawing as well as graphic design, with a strong knowledge of Adobe products along with the visual language of how work is viewed when printed and presented to the public. Using these skills, I am able to create meaningful designs whether the final product is hand drawn, digitally illustrated, or technical in its typography. My goal is to create visual tools that are communicative no matter the scope of the product or project. By developing an understanding of balance, readability, and hierarchy in form, I have advanced skills in guiding the eye of the viewer which can be adapted project to project.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design